(untitled) (Critical Journal of Social Sciences, 2026)
This review article examines the potential implementation of artificial intelligence (AI) and machine learning (ML) in digital governance in the Philippines. It addresses the need for a deeper understanding of specific application areas, ethical considerations, and essential policy and capacity-building strategies within the Philippine context. Using a secondary data collection and qualitative document analysis of eleven (11) sources, including academic journals, policy documents, and government reports, the study identifies promising areas for artificial intelligence (AI) and machine learning (ML) applications. These areas include citizen services, policy formulation, healthcare, criminal justice, public fiscal management, and e-governance. The review article also highlights key challenges and risks, such as ethical concerns, data quality and privacy, transparency and explainability, risk management, and the absence of a comprehensive legal framework. It proposes crucial policy and capacity-building strategies, developing a legal and ethical framework, training and upskilling programs, data governance, and prioritizing innovation and ethical practices. The findings suggest that strategically integrating artificial intelligence (AI) and machine learning (ML) could transform digital governance in the Philippines, provided that ethical considerations and capacity-building are prioritized.